آليات تحقيق التيسير في الفقه الإسلامي - حرشاو، رشيدة Hershaw, Rashidah (جامعة باتنه 1 - كلية العلوم الإسلامية, 2017)
يأتي هذا المقال ليتناول مسألة التيسير من جانبها العملي التحصيلي؛ بحيث يسعى الى توضيح وبيان المرتكزات العلمية والوسائل الاجرائية التي يعتمدها المجتهد أو المفتي لرفع الحرج عن المكلفين وتحقيق التيسير المنضبط. وتعرضت فيه إلى بيان مفهوم آليات التيسير، ثم قسمت هذه الآليات على ثلاثة مباحث، تحدثت في الأول منها عن الآليات الأصولية وتمثلت في: تفعيل مبدأ الاستحسان، مراعاة الخلاف والأخذ بالأخف. وخصصت الثاني للحديث عن الآليات الفقهية، وأهمها استثمار فقه البدائل مع نبذ التعصب المذهبي. وكان الأخير في الآليات المقاصدية وهي إعمال فقهي الموازنات والأولويات.
This artical comes to talk about facilitative from her effective practical collecting side, so that seeks to clarify the statement of the fundamental cornerstones of the process and means of procedure adopted by the hardworking or mufti to lift the embarrassement of assigned and uncontrolled facilitation. It was exposed to the statement of the concept of the facilitation mechanisms on three chapter, spoke in one of the mechanisms of fundamentalism represented in activating the principle of approval, talking into account the dispute over the introduction of AKAF, second allocated them to talk about jurisprudence mechanisms, the most important jurisprudence investment alternatives with the rejection of fanaticism. The latter in the MAKASID mechanisms; that it was fonctionment of budgets and priorities.
Keywords: فقه الإسلامي -- أصول الفقه -- الاستحسان -- فقه الموازنات -- مقاصد الشريعة